Database systems a practical approach to design, implementation, and management - Connolly, Thomas M. (Addison-Wesley, 2010)
This best-selling text introduces the theory behind databases in a concise yet comprehensive manner, providing database design methodology that can be used by both technical and non-technical readers. The methodology for relational Database Management Systems is presented in simple, step-by-step instructions in conjunction with a realistic worked example using three explicit phases-conceptual, logical, and physical database design.